The role of premotor and parietal cortex during monitoring of involuntary movement: A combined TMS and tDCS study. (November 2017) - Bruno, Valentina; Fossataro, Carlotta; Bolognini, Nadia; Zigiotto, Luca; Vallar, Giuseppe; Berti, Anna; Garbarini, Francesca
Abstract: Converging evidence on voluntary actions underlays the existence of a motor monitoring system able to compare the predicted and the actual consequences of our movements. In this context, both the premotor cortex (PMC) and the posterior parietal cortex (PPC) play a role in action monitoring and awareness. The present study explores the role of PMC and PPC in monitoring involuntary muscle contractions induced by transcranial magnetic stimulation (TMS) over the hand motor area. To this aim, the effects of transcranial direct current stimulation (tDCS) over PMC and PPC were examined. Thirty-six healthy subjects were asked to perform a motor monitoring task (i.e., to verbally report hand twitches induced by TMS) after 10 min of tDCS. Through three experiments, the effects of cathodal, anodal and sham tDCS over the left and the right hemispheres were compared. Our results show that cathodal tDCS over the right PMC does not affect the monitoring of involuntary movements. By contrast, tDCS over both the right and the left PPC affects motor monitoring, depending on the current polarity: while cathodal tDCS increases the feeling of phantom-like movements (which actually did not occur), anodal tDCS impairs the ability to detect involuntary hand twitches (which actually took place). These findings show that the PMC is not involved in motor monitoring of involuntary movements; rather, the PPC, where multisensory stimuli converge and are processed, seems to play a crucial role.